INTERACTIVE THEMATIC MAPPING FOR EFL EDUCATION: EXPLORING SDG 16 WITH JAPANESE AND COLOMBIAN UNIVERSITY STUDENTS - Perrem, John Guy; Habte-Gabr, Ezana Eyassu (LLT Journal: A Journal on Language and Language Teaching, 2025)
English language education has increasingly incorporated global issues to provide a link between classroom learning and real-world problems. The intent is that by examining such issues, students will engage with challenges while developing language skills in more purposeful ways. Acknowledging this, this study foregrounds the use of interactive online thematic maps for Sustainable Development Goal (SDG) 16 as the central pedagogical tool. SDG 16 focuses on peace, justice, and strong institutions. Responses from 35 Japanese and Colombian university students regarding their use of interactive online thematic maps were analyzed. Across five university EFL lessons, this cross-cultural study used a Likert-scale survey to evaluate how interactive online thematic maps supported vocabulary, reading, analytical thinking, and motivation. Lessons integrated interactive online SDG 16 maps with discussion-based classroom activities that encouraged exploration of indicators such as homicide, corruption, press freedom, and access to justice. Results indicate that interactive online maps enhanced language skills, critical thinking, and understanding of SDG 16. Findings suggest that interactive online maps provide a visually engaging way to link language learning with global citizenship education. This study demonstrates the potential of interactive online thematic maps to integrate sustainability topics into EFL and promote deeper cross-cultural and socio-political awareness.